Evaluación de la riqueza de especies de peces en las lagunas costeras mexicanas: Estudio de un caso en el Golfo de México - Pérez-Hemández, Marco Aurelio; Torres-Orozco, Roberto E (Revista de Biología Tropical, 2000)
We analyze the origin of knowledge about fish species richness in the Tuxpan-Tampamachoco estuarine system, in Veracuz, México. A complete inventory of the fish species known to date for this system (N=179) was elaborated from published lists and from sampling seagrass meadows of Tampamachoco Lagoon, which yielded 14 previously unknown species. W hen compared, the different Iists showed a low similarity that may reflect differences in sampling methods and collecting strategies. Current data suggest that fish species richness in Mexican coastal lagoons (Gulf of Mexico) is not related with ¡agoon surface area, as has been suggested, but with the number of inventories available for each lagoon, being these a reflection of the sampling effort. A sampling design for the assessment of fish species richness in estuarine systems should consíder: a) using the highest possíble varíety of samplíng fishing gears, b) col!ecting in al! microhabitat types and c) the preference of bimonthly or quarterly samplings for two or more years over monthly samplings in a single year